1994
DOI: 10.1104/pp.104.2.431
|View full text |Cite
|
Sign up to set email alerts
|

Development of Desiccation Tolerance during Embryogenesis in Rice (Oryza sativa) and Wild Rice (Zizania palustris) (Dehydrin Expression, Abscisic Acid Content, and Sucrose Accumulation)

Abstract: The ability of seeds to withstand desiccation develops during embryogenesis and differs considerably among species. Paddy rice (Oryza sativa 1.) grains readily survive dehydration to as low as 2% water content, whereas North American wild rice (Zizania palusfris var inferior [Fasset] Dore) grains are not tolerant of water contents below 6% and are sensitive to drying and imbibition conditions. During embryogenesis, dehydrin proteins, abscisic acid (ABA), and saccharides are synthesized, and all have been impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 30 publications
2
28
1
Order By: Relevance
“…The glass structure assures cell stability at the time of dehydration, since the high viscosity of glass can prevent the crystallization of chemical compounds, membrane fusion, and conformational changes of proteins (Hoekstra et al 2001). Still et al (1994) reported that in developing embryos of rice seeds, sucrose is accumulated linearly from 10 to 40 DAF and this accumulation pattern paralleled the increase we observed in LEA proteins ( Figure 5). Using synthetic models, Shimizu et al (2009) reported that LEA proteins are intrinsically disordered in solution but fold into α-helices during drying, and these proteins play a role in reinforcing the glassy matrix of oligosaccharides.…”
Section: The Roles Of Lea Proteins In the Desiccation Tolerance Of Risupporting
confidence: 68%
“…The glass structure assures cell stability at the time of dehydration, since the high viscosity of glass can prevent the crystallization of chemical compounds, membrane fusion, and conformational changes of proteins (Hoekstra et al 2001). Still et al (1994) reported that in developing embryos of rice seeds, sucrose is accumulated linearly from 10 to 40 DAF and this accumulation pattern paralleled the increase we observed in LEA proteins ( Figure 5). Using synthetic models, Shimizu et al (2009) reported that LEA proteins are intrinsically disordered in solution but fold into α-helices during drying, and these proteins play a role in reinforcing the glassy matrix of oligosaccharides.…”
Section: The Roles Of Lea Proteins In the Desiccation Tolerance Of Risupporting
confidence: 68%
“…On the other hand, the presence of other LEA proteins is not always correlated with stress tolerance. For example, comparative studies of wild rice and paddy rice showed that the intolerance of wild rice seeds to dehydration at low temperature is not due to an absence of, or an inability to synthesize, group 2 LEA/dehydrin proteins, ABA, or soluble carbohydrates (Bradford and Chandler, 1992;Still et al, 1994). Overproduction of a group 2 LEA protein from the resurrection plant Craterostigma in tobacco did not confer tolerance to osmotic stress (Iturriaga et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Along with other regulators of plant growth and development, ABA plays a major role in the control of embryo maturation and seed formation via regulation of storage reserve deposition, acquisition of desiccation tolerance as well as induction of primary dormancy and suppression of precocious germination (Still et al 1994;Bartels et al 1988;Gerjets et al 2010). Although more research dealing with mechanisms of ABA action has been conducted, many questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Although more research dealing with mechanisms of ABA action has been conducted, many questions remain unanswered. It is well known that ABA affects the induction of genes for some specific proteins (Still et al 1994;Mukherjee et al 2006;Cao et al 2007;Xiang et al 2008) and the inhibition of certain reserve mobilizing enzymes (Robertson et al 1989;Gómez-Cadenas et al 1999, 2001Bethke et al 2006). Some studies show that ABA also has the ability to modify the orientation of microtubules, a cytoskeletal element directing mRNA transport and localization, which may lead to the alteration of targeted synthesis of proteins within the cell (Shibaoka 1994;Klyachko 2003).…”
Section: Introductionmentioning
confidence: 99%